THE EFFECT OF PROFITABILITY AND LIQUIDITY ON VALUE COMPANIES WITH CAPITAL STRUCTURE AS INTERVENING VARIABLES - Samanoi Halowo Fau; Anskaria S. Gohae (SEAN Institute, 2022)
The scope of this research is a study of the effect of profieffectity (ROE) and liquidity (CR) on firm value (PBV) with capital structure (DER) as an intervening variable at AKR Corporindo Tbk in 2016-2020. The purpose of this study was to determine the effect of profitability (ROE) and liquidity (CR) on firm value (PBV) with capital structure (DER) as an intervening variable that analyzes the pattern of relationships between variables in the variable's cause and effect and to know the fact and indirect. This research is quantitative research with a path analysis approach. The results from substructure one show that partially pro partial (ROE) has no significant effect on capital structure (DER). Liquidity (CR) partly has a negative and significant impact on capital structure (DER), and the combined product of profitability (ROE) and liquidity (CR) on capital structure (DER) is 79,8%. Partial profitability (ROE) has a positive and significant effect on firm value (PBV), liquidity (CR) partially has a negative and significant impact on firm value (PBV), and capital structure (DER) has and significant effect on firm value (PBV). The combined impact of profitability (ROE), liquidity (CR), and capital structure (DER) variables on firm Value (PBV) is 30,2%.